(untitled) (Medico Legal Update, 2021)
Some isolates of bacteria were taken from various places inside the hospital, including operating theaters, corridors, ventilation areas, floors, and other samples were taken from patients suffering from antibiotic resistance. The study aims to discover the multiple resistant bacteria present in the hospital environment, to discover the extent of their resistance, and to detect the gene NDM-1, NDM-2, which when they are present, the bacteria are highly resistant. When a patient is infected with multiple resistant bacteria, he suffers from all antibiotic resistance and may lead to death, which is the biggest problem in the world today.